Platelet-to-Lymphocyte Ratio is Associated with the Mortality in Peritoneal Dialysis Patients (Iranian Journal of Kidney Diseases, 2021)
Introduction. Platelet-to-lymphocyte ratio (PLR) is widely used as an inflammatory marker and is associated with poor prognosis in some diseases, such as cardiovascular diseases and malignancies. However, the association between the PLR and all-cause mortality in peritoneal dialysis (PD) patients is unclear. Methods. A total of 939 patients were enrolled. The X-tile program was performed to calculate the optimal cut-off values for the PLR, and the patients were divided into three groups according to the cut-off values: a low PLR group (< 108.33), medium PLR group (108.33 to 257.50), and high PLR group (> 257.50). Multivariate analysis was performed to assess the prognostic value of PLR. The primary end point was all-cause mortality. Results. Of the 939 patients, the mean age was 49.9 years, and 57% of the patients were male. During a median follow-up of 27.5 months (interquartile range, 13.6-41.6 months), 221 (23.5%) died, in whom 114 (51.6%) deaths were attributed to cardiovascular mortality. Patients in the high PLR group had a higher mortality rate than patients in the low PLR group (log rank = 13.75, P < .001). The 1-year and 3-year overall survival rates were 88.9% and 71.7% for patients in the high PLR group compared with 98.6% and 86.2% for patients in the low PLR group, respectively. Similarly, multivariate Cox regression analysis showed that the mortality rate was higher in the high PLR group than in the low PLR group (HR = 1.64, 95% CI: 1.02 to 2.63, P < .05). Conclusion. An increased PLR value was independently associated with all-cause mortality in PD patients.